2016
DOI: 10.1038/srep34636
|View full text |Cite
|
Sign up to set email alerts
|

A novel three-axis cylindrical hohlraum designed for inertial confinement fusion ignition

Abstract: A novel ignition hohlraum for indirect-drive inertial confinement fusion is proposed, which is named three-axis cylindrical hohlraum (TACH). TACH is a kind of 6 laser entrance holes (LEHs) hohlraum, which is orthogonally jointed of three cylindrical hohlraums. Laser beams are injected through every entrance hole with the same incident angle of 55°. A view-factor simulation result shows that the time-varying drive asymmetry of TACH is less than 1.0% in the whole drive pulse period without any supplementary tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…Six-LEH hohlraums [13][14][15] , as shown in Figure 15, have one more rotational degree of freedom and two more laser entrance directions compared to cylindrical targets. It is very difficult to align such a hohlraum with the TAS, which is designed for use with a cylindrical hohlraum.…”
Section: Space-diagonal Rotation Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Six-LEH hohlraums [13][14][15] , as shown in Figure 15, have one more rotational degree of freedom and two more laser entrance directions compared to cylindrical targets. It is very difficult to align such a hohlraum with the TAS, which is designed for use with a cylindrical hohlraum.…”
Section: Space-diagonal Rotation Sensormentioning
confidence: 99%
“…Over the past 3 years, work has shown that a spherical hohlraum with six laser entrance holes (LEHs) [13, 14] or a three-axis cylindrical hohlraum (TACH) [15] , which contains three orthogonally joined cylindrical hohlraums and six LEHs – with high symmetry on a capsule, and low possibility of plasma jet generation – seems superior to a cylindrical target. With more LEHs to be positioned and the shooting laser from six directions to be aligned, this target poses new challenges for alignment.…”
Section: Introductionmentioning
confidence: 99%
“…在最近的研究工作中我们又提出了六通柱腔 [42] (图22(a))、三轴柱腔 [43] [45] 、Au-U-Dy鸡尾酒黑腔 [46] 图 23 (网络版彩图)神光Ⅲ原型装置上的纯Au腔和UN涂 层U腔X光能谱对比 [47] Figure 23 (Color online) The X-ray spectra from Au hohlraum and UN-coated DU hohlraum on SG-Ⅲ prototype [47].…”
Section: 六通柱腔和三轴柱腔unclassified
“…However, the overlap and cross of laser beams may arouse nonlinear phenomena and complicated laser-plasma interaction issues [35], such as the daunting SRS and CBET. Recently, a spherical hohlraum with 6LEHs [36] and a novel hohlraum with a three-axis cylindrical hohlraum [37,38], all of which utilize a single-cone beam without any supplementary technology of beam phasing, are proposed to improve these issues, especially the propagation of the inner-cone beams. These hohlraum configurations have natural superiority in maintaining high drive symmetry during the entire capsule implosion process [37][38][39].…”
Section: Nuclear Fusionmentioning
confidence: 99%